Children's Anxiety Levels Are Associated with Family Support and Length of Hospitalization - Heri Saputro; Eva Agustina Yalestyarini; Intan Fazrin; Nasirotun Nikmah (Universitas Tribhuwana Tunggadewi, 2026)
Anxiety is an emotional reaction caused by nonspecific factors that can cause feelings of worry, discomfort, and threat. The emergence of anxiety is usually influenced by several factors. Similarly, anxiety is experienced by children who are hospitalized. Patients treated in the Trigger Room need the support of their family who has a close relationship with the patient. This family support is the most important form of support in carrying out therapy and reducing the patient's anxiety level where anxiety is a condition that arises within a person characterized by deep and persistent feelings of fear. This study aimed to analyze the effect of family support and length of hospitalization on anxiety levels in children. The research design used an analytical survey with a cross-sectional approach. The sample consisted of 31 respondents. The independent variables were family support and length of hospitalization, while the dependent variable was children's anxiety level. The instrument used the Spence Children's Anxiety Scale. The statistical analysis was the chi-square test. The results of the study showed a p-value = 0.001 (Chi-square test). The study concluded that there is a significant relationship between family support and length of hospitalization with anxiety levels in children treated in the Trigger Room of Dr. Iskak Tulungagung Regional Hospital. It is recommended that nursing services be improved to patients so that the average length of hospitalization among children can be reduced and family support can be increased.